Knowledge, Attitude And Practice (Kap) On Occupational Noise Exposure Among Workers In The Palm Oil Mill Industry - Nur Syamimi, Amran (2025)
Occupational noise exposure has considerable health concerns, especially in industries such as palm oil mills. This study evaluated workers' knowledge, attitudes, and practices (KAP) focusing on occupational noise exposure in the palm oil mill industry. Data were obtained from 303 respondents using a standardized questionnaire and analyzed for reliability, demographic trends, and correlations between KAP variables. While a significant percentage of workers indicated medium to high levels of knowledge and positive attitudes, major gaps in comprehension persisted, with 25.4% demonstrating extremely low knowledge. Practices were encouraging, with 61.7% implementing effective measures. However, 24.8% reported very low levels of practice. A moderate negative correlation was found between knowledge, attitude, and practice, showing that increasing awareness does not always convert into proactive behaviors. In contrast, the positive relationship between attitude and practice underscored the necessity of creating good attitudes for effective noise reduction procedures. The study emphasises the importance of focused educational initiatives, regulatory changes, and practical interventions for improving awareness and encouraging safer practices. These activities are crucial for reducing occupational noise exposure concerns, guaranteeing worker safety, and creating a healthier and more productive workplace.